Peran Pemerintah Daerah Dalam Peningkatan Kesejahteraan Petani Melalui Program Pertanian Terpadu di Kabupaten Pinrang - Muh. Rafly Syahdinrah (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2026)
The agricultural sector plays a strategic role in supporting regional economic development, particularly in Pinrang Regency, which is recognized as one of the major agricultural areas with significant potential in food crops and horticultural commodities. However, efforts to increase agricultural productivity continue to face various challenges, including limited access to agricultural technology, inadequate production facilities, insufficient training opportunities, and weak institutional capacity among farmers. This study aims to analyze the role of the Pinrang Regency Government in the development of food crop and horticultural subsectors, as well as the provision of agricultural machinery and equipment. The study employed a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis involving officials from the Food Crops, Horticulture, and Plantation Office, farmer groups, and individual farmers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the Pinrang Regency Government has implemented various agricultural development programs, including the provision of superior seeds, integrated agricultural extension services, agricultural machinery assistance, and farmer group mentoring. These programs have contributed to improving agricultural productivity and farming efficiency. Nevertheless, several challenges remain, such as limited regional budgets, weak inter-agency coordination, and unequal distribution of assistance among farmers. Therefore, stronger collaboration among stakeholders, improved extension and mentoring services, and evidence-based policymaking are required to support sustainable agricultural development in Pinrang Regency.